Prevalence and Characteristics of Acquired Coronary Fistulas After Successful Revascularization of Chronic Total Occlusion - Fan, Rong; Tan, Haipeng; Song, Yanan; Yao, Wang; Fan, Min; Huang, Zheyong; Ge, Junbo (Frontiers in Cardiovascular Medicine, 2021)
Background and Objectives: Acquired coronary fistulas (ACFs) are rare coronary artery abnormalities in CTO patients. It has been found after revascularization, and may cause fluster during the CTO PCI. How to distinguish between ACFs and Coronary perforation (CP) is very important for the CTO operators. CTO reopening may reveal microchannel of the advential vascular layers. Some of ACFs have been seen after revascularization. This study aimed to investigate the characteristics of ACFs after successful chronic total occlusion percutaneous coronary intervention (CTO PCI). Methods: The clinical and procedural characteristics, medical history, and findings in electrocardiography, echocardiography and coronary angiography were collected from 2169 consecutive patients undergoing CTO PCI between January 2018 and December 2019 and analyzed retrospectively. Results: 1844 (85.02%) underwent successful CTO PCI with complete revascularization. ACFs were found in 49 patients (2.66%): The majority of patients with ACFs were male (81.63% vs. 60.78%; p=0.016) and younger (62.8 vs. 66.69 years; p=0.003), had a history of myocardial infarction (MI) or Q-wave (69.39% vs. 54.21%; p=0.035); 38 (77.55%) patients had multiple fistulas (>3), and ACFs affected multiple branches of the CTO vessel (>3) in 29 (59.18%) patients. None had pericardial effusion, tamponade and hemodynamic abnormality before or after PCI. Conclusion: ACFs after successful CTO PCI are mainly present in young and male patients with a history of MI, and often involve multiple fistulas and distal CTO vessel.